2016
DOI: 10.1103/physrevlett.117.276805
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Imaging of Negative Differential Resistance on the Atomic Scale

Abstract: Negative differential resistance remains an attractive but elusive functionality, so far only finding niche applications. Atom scale entities have shown promising properties, but viability of device fabrication requires fuller understanding of electron dynamics than has been possible to date. Using an all-electronic time-resolved scanning tunneling microscopy technique and a Green's function transport model, we study an isolated dangling bond on a hydrogen terminated silicon surface. A robust negative differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 32 publications
2
50
0
Order By: Relevance
“…The NDR phenomenon was first observed by Leo Esaki in tunnel diodes 30 . It has been observed that DBs on degenerately doped silicon surfaces also exhibit NDR [27][28][29] . Figure 1a displays the I(V) spectroscopy of a DB on a degenerately n-doped hydrogen-terminated Si(100).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NDR phenomenon was first observed by Leo Esaki in tunnel diodes 30 . It has been observed that DBs on degenerately doped silicon surfaces also exhibit NDR [27][28][29] . Figure 1a displays the I(V) spectroscopy of a DB on a degenerately n-doped hydrogen-terminated Si(100).…”
Section: Resultsmentioning
confidence: 99%
“…Since this process is inelastic, this transition is slow. Direct measurement of the rates shows that the rate electrons pass from the conduction band to the (+/0) level is at least two orders of magnitude slower than the rate to reach the (0/-) level from the conduction band 29 . This slow inelastic process is the origin of NDR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, negative differential conductance is not restricted to molecular systems and has been found in inorganic materials as well, provided they feature discrete energy levels suitable for electron transport [10]. It has been observed, for example, in the tunnelling characteristic of Cl vacancies in NaCl thin films or of band-gap states in boron-or hydrogen-terminated Si(111) [11][12][13]. Also the conductance through Gd nanowires self-assembled on Si(110) displays a pronounced NDR region at negative bias [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the properties of single dopants in semiconductors have recently attracted significant attention because CMOS devices are now entering the regime where single dopants can affect device properties 17 . In addition, several studies have demonstrated that single dopants can serve as the fundamental component of future devices, for example as qubits for quantum computation 18 and quantum memory 19 , and as single atom transistors 20,15 . Future devices may also incorporate other atomic-scale defects, such as the silicon dangling bond (DB) which can be patterned with atomic precision with STM lithography 21 .…”
mentioning
confidence: 99%